A prion-like domain of TFEB mediates the co-aggregation of TFEB and mHTT. Issue 2 (1st February 2023) - Yang, Junsheng; Xu, Huilin; Zhang, Chaoyue; Yang, Xiaotong; Cai, Weijie; Chen, Xiaoli
ABSTRACT: The aggregation of mutant HTT (huntingtin; mHTT) is a hallmark of Huntington disease (HD). mHTT aggregates interact and sequester dozens of proteins and affect diverse key cellular functions. Here we report that TFEB (transcription factor EB), a master regulator of lysosome biogenesis and autophagy, is yet another protein that co-aggregates with mHTT. We also found the mHTT-TFEB co-aggregation is mediated by a prion-like domain (PrLD) near the N terminus of TFEB. Our findings point out a possible limitation for therapeutic strategies targeting TFEB to clear mHTT, and also provided a possible explanation for controversies that TFEB overexpression lowered soluble mHTT in some HD models but failed to reduce mHTT aggregates or HD pathology in others. Moreover, we found that TFE3, another MiT family transcription factor that shares overlapping functions with TFEB, lacks PrLD and does not co-aggregate with mHTT, and thus might serve as an alternative drug target for HD.